THE EFFECT OF YOUTUBE-BASED LEARNING ON ARABIC LEARNING MOTIVATION AND OUTCOMES AT MTS AL-ABRAR: A QUASI-EXPERIMENTAL STUDY - Khoirunnisa Nasution; Ria Rafita Supriani; Isra Hayati Darman (Al Ibrah: Journal of Arabic Language Education, 2026)
This study aims to examine the effect of YouTube-based learning on students’ motivation and learning outcomes in Arabic at MTs Al-Abrar Islamic Boarding School. A quasi-experimental design with a pretest-posttest control group was employed. The participants were divided into an experimental group and a control group. Data were collected using a motivation questionnaire and learning achievement tests, and analyzed using a t-test. The results showed a significant difference between the two groups (p < 0.05), indicating that YouTube-based learning effectively improves students’ motivation and learning outcomes. This means that there is a significant influence of the use of YouTube media on increasing student learning interest in learning Arabic. For further research, it is recommended that research be conducted at different educational levels or subjects to assess the consistency of the influence of YouTube media on learning outcomes. The use of a long-term (longitudinal) research design is highly recommended to measure the impact of YouTube use on student knowledge in more depth. الملخص أثر استخدام منصة يوتيوب في زيادة اهتمام الطلاب بتعلم اللغة العربية في مدرسة الأبرار الإسلامية الداخلية. تهدف هذه الدراسة إلى بحث أثر التعلم القائم على يوتيوب على دافعية الطلاب ونتائج تعلمهم للغة العربية. وقد استُخدم تصميم شبه تجريبي مع مجموعة ضابطة واختبار قبلي وبعدي. قُسّم المشاركون إلى مجموعتين: تجريبية وضابطة. جُمعت البيانات باستخدام استبيان الدافعية واختبارات التحصيل الدراسي، وحُللت باستخدام اختبار t. أظهرت النتائج وجود فرق دال إحصائيًا بين المجموعتين (p < 0.05)، مما يشير إلى أن التعلم القائم على يوتيوب يُحسّن بشكل فعال دافعية الطلاب ونتائج تعلمهم. وهذا يعني وجود تأثير كبير لاستخدام منصة يوتيوب في زيادة اهتمام الطلاب بتعلم اللغة العربية. ولإجراء المزيد من البحوث، يُوصى بإجراء دراسات على مستويات تعليمية أو مواد دراسية مختلفة لتقييم مدى اتساق تأثير منصة يوتيوب على نتائج التعلم. كما يُوصى بشدة باستخدام تصميم بحثي طويل الأمد (طولي) لقياس أثر استخدام يوتيوب على معارف الطلاب بشكل أعمق.